Estimation of Antioxidants Activity Through DPPH Inhibition Levels in Patients with Chronic HPV 16 Cervicitis (Medico Legal Update, 2020)
In the present study, the DPPH scavenging activity from the primary methods to estimation the antioxidantsactivity in the body by an inverse relation between them. So, the levels of DPPH scavenging activity isreduced in the patient with HPV16 genotype chronic cervicitis (G3= 43.01±2.74 in the serum, G3= 9.73±1.53in the mucus) and without (G2= 47.22±4.50 in the serum, G2= 15.51±1.41 in the mucus)compared withhealthy women (G1= 64.79±4.87 in the serum, G1= 21.24±3.62 in the mucus), this is a return to loweringantioxidants in the patients compared with healthy women. The deterioration in the antioxidants levels cancause cancer in the future or delay the response of the medication to inflammation.